Effects of organic trace minerals chelated with oligosaccharides on growth performance, blood parameters, slaughter performance and meat quality in sheep - Zhang, Runze; Wei, Manlin; Zhou, Jianqun; Yang, Zaibin; Xiao, Ming; Du, Liu; Bao, Meili; Ju, Ji; Dong, Chenyang; Zheng, Yongjie; Bao, Hailin (Frontiers in Veterinary Science, 2024)
The present study assessed the effects of oligosaccharide-chelated organic trace minerals (OTM) on the growth performance, digestive enzyme activity, blood parameters, slaughter performance, and meat quality indexes of mutton sheep. A total of 60 East Ujumuqin × small-tailed Han crossbred mutton sheep were assigned to two groups (ten duplicates per group) by body weight (26.12 ± 3.22 kg) according to a completely randomized design. Compared to the CON group, the results of the OTM group showed:(1) no significant changes in the initial body weight, final body weight, dry matter intake, average daily gain, and feed conversion ratio (P > 0.05); (2) the activities of trypsin, lipase, and amylase in the jejunum were significantly increased (P < 0.05); (3) serum total protein, albumin, and globulin of the blood were significantly increased (P < 0.05), and the growth factor interleukin (IL)-10 was significantly higher (P < 0.05), while IL-2, IL-6, and γ-interferon were significantly lower (P < 0.05). Immunoglobulins A, M, and G were significantly higher (P < 0.05); (4) the live weight before slaughter, carcass weights, dressing percentage, eye muscle areas, and GR values did not differ significantly (P > 0.05); (5) shear force of mutton was significantly lower (P < 0.05), while the pH45min, pH24h, drip loss, and cooking loss did not show a significant difference (P > 0.05). The content of crude protein was significantly higher (P < 0.05), while the ether extract content was significantly reduced (P < 0.05), but no significant difference was detected between moisture and ash content; (6) the total amino acids, essential amino acids, semi-essential amino acids, and umami amino acids were significantly increased (P < 0.05). Although umami amino acids were not significant, the total volume increased (P > 0.05). Among these, the essential amino acids, threonine, valine, leucine, lysine in essential amino acids and arginine were significantly increased (P < 0.05). Also, non-essential amino acids, glycine, serine, proline, tyrosine, cysteine, and aspartic acid, were significantly higher (P < 0.05). The content of alanine, aspartate, glutamic acid, phenylalanine, and tyrosine in umami amino acids was significantly higher (P < 0.05).